The pharmacological basic of therapeutics - Goodman, Louis Sanford; Gilman, Alfred (The Macmillan Company, 1965)
The objectives of the book is the correlation of pharmacology with related medical sciences, the reinterpretation of the actions and the uses of drugs from the viewpoint of important advances in medicine, and the placing of emphasis on the applications of pharmacodynamics to therapeutics. A textbook, a template for prescribing of drugs in daily practice.
Keywords: léčivé přípravky; farmaceutický laborant; terapie; Pharmaceutical Preparations; Pharmacy Technicians; farmacie a farmakologie; farmakologické jevy; Pharmacological Phenomena; farmakoterapie; Therapeutics